Statistical nature of the incipient plasticity in amorphous alloys - Nag, Shankha (2022)
Statistical analyses of the first pop-in stress data, obtained by spherical tip-nanoindentation experiments on different metallic glasses (MGs) with tip radius, Ri, loading rate,P˙, and structural state of the glass as experimental variables, show that the 3-parameter bimodal Weibull distribution best captures the stochastic nature of the incipient plastic strengths. Significant bimodality in the strength distributions was observed only when a larger Ri and P˙ are employed. We hypothesize that the stress required for shear band nucleation has to exceed a critical value over a characteristic distance over which the stress gradients are minimum to rationalize the bimodality.